”All’s well the end’s well”? Challenges and lessons learnt of an international pedagogy bachelor program introduced in the middle of the COVID 19 pandemic - Dezső Renáta Anna (II. Rákóczi Ferenc Kárpátaljai Magyar Főiskola, 2024)
Abstract. During the 2019 spring semester, the academic staff of the Institute of Educational Sciences (IES) at the Faculty of Humanities and Social Sciences (FHSS) at the University of Pecs (UP) developed a new international bachelor program – the author, being the program manager –, that had existed before exclusively in Hungarian. The license of the Pedagogy BA program with Intercultural Educational Assistant Specialization was issued in the summer of 2019 (OH 2019), so spring 2020 was the head start for admission interviews. Out of 12 accepted applicants 11 students from China, Mongolia, Vietnam, Turkey, Slovakia, and the Netherlands started their studies in September 2020 followed by others in September 2021 and September 2022 from further countries, such as Qatar, Laos, Mauritius, Colombia, Russia, and Kosovo (Bergan–Restoueix 2009). By the 2023 spring semester – the 6th one of their studies – there are 10 students busy with their thesis writing heading for their final exam on the program.
https://opac3.brff.monguz.hu/hu/record/-/record/bibBRF00014390
Keywords: challenge; bachelor program; Covid 19 Pandemic; education